Radiation and humankind : proceedings of the First Nagasaki Symposium of International Consortium for Medical Care of Hibakusha and Radiation Life Science, Nagasaki, Japan, 21-22 February 2003 - Symposium of International Consortium for Medical Care of Hibakusha and Radiation Life Science (1st : 2003 : Nagasaki, Japan); Yoshisada Shibata (Amsterdam : Elsevier, 2003)
42